Constructing a Theology of Solidarity as a Praxis of Christian Faith - Maruli Tua Tampubolon; Ruben Nesimnasi (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2026)
Solidarity is a significant theme in Christian theology that connects the relationship between God and human responsibility toward others. Amid the realities of poverty, injustice, and religious pluralism, this study aims to examine the theology of solidarity through hermeneutical, socio-historical, and ecclesiological perspectives, while also exploring the roles of God and humanity in embodying solidarity as a praxis of faith. This research employs a library research method with a descriptive-analytical approach to the thoughts of contemporary theologians. The findings indicate that solidarity is rooted in the kenosis of Jesus Christ as the manifestation of God's presence in human suffering. The Church is called to become a sacrament of solidarity that embodies love, justice, and liberation, while human beings are called to act as God's partners in promoting the common good, peace, and interreligious dialogue. This study concludes that solidarity is not merely an ethical attitude but a praxis of faith that integrates discipleship, social responsibility, and the witness of the Gospel in everyday life.